Enhancing Sharia Financial Literacy Through Educational Initiatives on Sharia Microfinance Institutions within the Context of the Mujahadah Mosque Vicinity in Rintis Village, Pekanbaru - Wali Saputra (Aksi Kita: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service initiative is designed to elevate Sharia financial literacy through the educational outreach concerning Sharia Micro Finance Institutions (LKMS) targeted at the residents within the vicinity of Masjid Mujahadah, Rintis Village, Pekanbaru. The predominant context for this program stems from the community's insufficient comprehension of Islamic financial principles coupled with the suboptimal engagement with sharia financial services. The methodological framework encompasses a preparatory stage, the execution of participatory educational sessions over a two-day period, evaluative measures employing pre-tests and post-tests, as well as subsequent activities that include the establishment of a Sharia Financial Literacy Group. The outcomes of this initiative indicated a notable enhancement in the participants’ grasp of fundamental concepts of Islamic economics and the application of sharia microfinance products. Furthermore, this initiative fosters a collective social commitment towards the continuous pursuit of knowledge in a mosque-centered, sustainable manner. This endeavor substantiates the efficacy of community-oriented educational strategies and religious establishments as a potent mechanism for augmenting the financial inclusion of Sharia at the grassroots level.